Relationship between traditional Malaysian vegetables (ulam) intake and cognitive status among middle-aged adults from low cost residential areas - Yee, Xing You; Suzana Shahar; Hasnah Haron; Hanis Mastura Yahya; Normah Che Din (Penerbit Universiti Kebangsaan Malaysia, 2019)
Ulam is fresh traditional Malaysian vegetables which normally consumed in raw form or after a short blanching process. It contains high antioxidants and polyphenols. However, there is limited study about the relationship between ulam consumption and cognitive status. Thus, a cross sectional study was conducted to determine the relation with cognitive function among 132 middle-aged Malays adults (45-59 years old), recruited by convenient sampling from low income residences in Klang Valley. Respondents were interviewed to obtain data on sociodemography, dietary intake and total ulam intake and also measured for anthropometric parameters at respective community centres. Cognitive status was measured using Digit Span (attention and working memory), Rey auditory verbal learning test (RAVLT) (verbal memory) and comprehensive trail making test (CTMT) (cognitive flexibility). The average ulam intake by the respondents was 15.1 ± 8.2g/day and the top five highest consumed ulam were petai (68.1%), pucuk paku (62.9%), ulam raja (56.8%), pegaga (54.6%) and kesum (44.7%).There was a significant correlation between ulam intake with Digit Span (r = 0.265, p = 0.006), total immediate recall of RAVLT (r = 0.427, p < 0.001) and CTMT (r = 0.257, p = 0.007). Analysis of multiple regression indicated that total ulam intake was a significant predictor for Digit Span (R2 = 0.152, p < 0.05), RAVLT (R2 = 0.335, p = 0.001) and CTMT (R2 = 0.310, p < 0.001). In conclusion, this study showed that ulam has the potential to protect against cognitive decline, however, randomized control trials should be conducted to determine the efficacy of the ulam as neuroprotective agent.